LANGUAGE LEARNING STRATEGIES OF UNDERGRADUATE EFL STUDENTS - Mega Lestari; Achmad Yudi Wahyudin (fsip.teknokrat.ac.id, 2020)
This study attempts to explore the language learning strategies used by the students’ who take English Literature study programs in English as a foreign language (EFL) setting. This study involves 76 participants asked to fulfill a questionnaire called Strategy Inventory for Language Learning (SILL) developed by Oxford (1990). The result of this research showed that metacognitive has been the most frequently used strategy followed by social and compensation strategies while affective strategies become the least strategy used by the students. This research could be meaningful insight for other researches or the students to analyze the language learning strategies used by the students and be meaningful to know the language learning strategies that appropriate especially in the field of the second language.